Association of HLA-DR and -DQ genes with narcolepsy in Koreans: comparison with two control groups, randomly selected subjects and DRB11501-DQB10602--positive subjects - Roh, Eun Youn; Park, Myoung Hee; Park, Hyejin; Park, Doo-Heum; Choi, Jong-Bae; Kim, Seog Ju; Jeong, Do-Un (Human Immunology, 2006)
The purpose of this study was to investigate the association of human leukocyte antigen (HLA) class II alleles with narcolepsy-cataplexy susceptibility in Koreans. The distribution of HLA-DRB1 and -DQB1 alleles and presence or absence of DRB3/4/5 alleles were examined in 60 narcoleptic patients with clear-cut cataplexy, and the results were compared with two groups of healthy controls: 200 randomly selected controls and 144 DRB1*1501-DQB1*0602 positive controls. All of the narcoleptic patients were DRB1*1501 and DQB1*0602 positive, and their frequencies were significantly higher in patients than in random controls (100% vs 17.0%, p(c) = 2.3 x 10(-30), OR = 583.96; 100% vs 16.5%, p(c) = 3.9 x 10(-31), OR = 605.00). The HLA association in Koreans was as tight as that reported in Japanese. Several DRB1 (*0101, *0405, *0901) and DQB1 alleles (*0303, *0401, *0501, *0601, *0604) were found to have weak protective effects against narcolepsy. DRB4 showed strong protective effect, and this was also significant when compared with DRB1*1501-DQB1*0602 positive controls (18.3% vs 44.4%, p(c) = 0.001, OR = 0.28). DRB3 (OR = 1.86) and DQB1*0301 (OR = 2.45) were found to have weak predisposing effect, when compared with DRB1*1501-DQB1*0602 positive controls. The protective effect of DRB4 has to be further studied in other populations.